2017
DOI: 10.1177/0363546517717698
|View full text |Cite
|
Sign up to set email alerts
|

Heel-Rise Height Deficit 1 Year After Achilles Tendon Rupture Relates to Changes in Ankle Biomechanics 6 Years After Injury

Abstract: Height obtained during the single-leg standing heel-rise test performed 1 year after ATR related to the long-term ability to regain normal ankle biomechanics. Minimizing tendon elongation and regaining heel-rise height may be important for the long-term recovery of ankle biomechanics, particularly during more demanding activities such as jumping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 43 publications
(55 reference statements)
5
109
1
3
Order By: Relevance
“…Not surprisingly, the maximal height achieved during the heel‐rise test was substantially lower (32%) on the injured side, which corroborates that of several studies . It has been suggested that this deficit reflects an increase in tendon length, which is supported by the present data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Not surprisingly, the maximal height achieved during the heel‐rise test was substantially lower (32%) on the injured side, which corroborates that of several studies . It has been suggested that this deficit reflects an increase in tendon length, which is supported by the present data.…”
Section: Discussionsupporting
confidence: 93%
“…The recovery time after an Achilles tendon rupture is typically several months, and irrespective of the initial treatment, complete functional outcome is often not reached . The rehabilitation of ruptured Achilles tendons includes varying loading programs, albeit without a real consensus with regards to the magnitude and when to initiate the loading .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve similar jump height, the knee performs greater peak power during the takeoff phase as well as relative work over both takeoff and landing phases as suggested by our findings. Prior work by Brorsson et al, found that tendon elongation and calf endurance related, respectively, to ankle kinematics and kinetics during jumping. While this study was not designed to allow for correlational analysis, it may be that the tendon elongation observed in this group of individuals underlies changes in biomechanics.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, studies have identified focal deficits in plantar flexor strength at 10 or more years following rupture . Furthermore, recent studies have identified altered ankle kinetics and kinematics as well as a shift of lower extremity peak power generation during running and jumping tasks from the ankle to the knee in individuals an average of 6 years following rupture …”
mentioning
confidence: 99%
See 1 more Smart Citation